A real-world pharmacovigilance study of FDA adverse event reporting system (FAERS) events for bimekizumab - Lin, Zhuomiao; Yu, Xihui; Yang, Meiqing; Xu, Jialan; Zhong, Jiahong (Frontiers in Pharmacology, 2026)
BackgroundBimekizumab, a humanized monoclonal antibody, exerts its therapeutic effect by inhibiting interleukin-17A/F and is indicated for the treatment of moderate-to-severe plaque psoriasis in adult patients. However, the long-term safety profile of bimekizumab remains under evaluation. In this study, adverse events were analyzed using data from the US Food and Drug Administration’s Adverse Event Reporting System (FAERS).MethodsWe analyzed adverse event reports in FAERS from the third quarter of 2021 to the fourth quarter of 2024, with bimekizumab identified as the primary suspected drug. The analytical methods included the Reported Odds Ratio, Proportional Reporting Ratio, Bayesian Confidence Propagation Neural Network, and Multi-Item Gamma Poisson Shrinker.ResultsA total of 2,744 suspected adverse event cases with bimekizumab as the major suspected drug were collected from the FAERS database in this study. The results showed that common clinical adverse events of bimekizumab included injection site pain, fatigue, pruritus, headache, arthralgia, rash, pain, oesophageal candidiasis, diarrhea. In addition, we detected probable unexpected adverse events using disproportionality analysis, such as depression.ConclusionWe identified potential new adverse events associated with bimekizumab through disproportionate analysis of extensive real-world data from the FAERS database. These findings enable healthcare professionals and pharmacists to prioritize effective management of high-risk adverse events, optimize drug utilization in clinical settings, and enhance patient medication safety.